Psychosocial impact of war on the social and emotional development of young learners: An integrative review of Literature - Peter J.O. Aloka; Oluwakemi Ajayi; Lilian Zindoga; Nzukiso Mnyamana (Perspectives in Education)
The psychological impacts of war on young learners' social and emotional development are examined in this integrated review. Not only can war and armed conflict have a profound influence on individual children, but they also negatively affect the entire family system. The difficulties associated with relocation, migration, and acclimatisation to new conditions exacerbate the repercussions of war. Instead of growing and developing in a safe, predictable, emotionally and physically healthy environment, children are faced with war. Children who have witnessed or experienced conflict are more likely to face psychosocial difficulties, which could seriously jeopardise their social, emotional, cognitive, and physical growth. By combining the results of a wide range of studies, the review demonstrates how exposure to armed conflict significantly alters children's and teenagers' developmental trajectories. The results show that trauma-related problems are common, social behaviours have changed, and the foundations of education are being undermined. The review emphasises the necessity for targeted policies and practices that address the unique needs of war-affected youth, advocating for a holistic approach to foster resilience and recovery. Furthermore, the review underscores the importance of creating social interaction and collaborating with international organisations to offer peace education as a subject to bring social cohesiveness to a warring nation.